Enhanced Memory for Vocal Melodies in Autism Spectrum Disorder and Williams Syndrome. Issue 6 (4th January 2021) - Weiss, Michael W.; Sharda, Megha; Lense, Miriam; Hyde, Krista L.; Trehub, Sandra E.
Abstract: Adults and children with typical development (TD) remember vocal melodies (without lyrics) better than instrumental melodies, which is attributed to the biological and social significance of human vocalizations. Here we asked whether children with autism spectrum disorder (ASD), who have persistent difficulties with communication and social interaction, and adolescents and adults with Williams syndrome (WS), who are highly sociable, even indiscriminately friendly, exhibit a memory advantage for vocal melodies like that observed in individuals with TD. We tested 26 children with ASD, 26 adolescents and adults with WS of similar mental age, and 26 children with TD on their memory for vocal and instrumental (piano, marimba) melodies. After exposing them to 12 unfamiliar folk melodies with different timbres, we required them to indicate whether each of 24 melodies (half heard previously) was old (heard before) or new (not heard before) during an unexpected recognition test. Although the groups successfully distinguished the old from the new melodies, they differed in overall memory. Nevertheless, they exhibited a comparable advantage for vocal melodies. In short, individuals with ASD and WS show enhanced processing of socially significant auditory signals in the context of music. Lay summary: Typically developing children and adults remember vocal melodies better than instrumental melodies. In this study, we found that children with Autistic Spectrum Disorder, who have severe social processing deficits, and children and adults with Williams syndrome, who are highly sociable, exhibit comparable memory advantages for vocal melodies. The results have implications for musical interventions with these populations.